PENYELESAIAN MALADMINISTRASI MELALUI LEMBAGA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN KALIMANTAN BARAT BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2008 TENTANG OMBUDSMAN REPUBLIK INDONESIA - NIM. A1011181069, VELSA NURFITRIANTI (Jurnal Fatwa Hukum, 2023)
ABSTRACT The Ombudsman Institute of the Republic of Indonesia has the duty to receive reports on alleged administration of public services. The public does not need to bother reporting all forms of administration to the Ombudsman of the Republic of Indonesia. Likewise with the Ombudsman of the Republic of Indonesia West Kalimantan Representative who provides the widest possible access to people who directly experience acts of maladministration committed by implementing officials and/or public service providers. Since the beginning of 2022 until July, the Ombudsman of the Republic of Indonesia Representative for West Kalimantan has received 275 reports of complaints of alleged maladministration.This study discusses the Ombudsman of the Republic of Indonesia Representative of West Kalimantan in processing reports of alleged maladministration and the factors that hinder the process of completing the report and also the efforts made by the Ombudsman of the Republic of Indonesia Representative of West Kalimantan if there are reports that are not resolved. This research uses a type of sociological legal research with an empirical approach or field research, namely studying the applicable legal provisions and what happens in reality in society. According to the nature of this research is descriptive analysis. The object of this research is the West Kalimantan Representative Ombudsman Institute. The techniques used are document studies, interviews and observation.The results of the study show that at the Ombudsman of the Republic of Indonesia Representative of West Kalimantan the most frequently reported types of alleged maladministration throughout 2022 are protracted delays, acting inappropriately, and not providing services. Factors that hinder the Ombudsman of the Republic of Indonesia West Kalimantan Representative in the process of completing the report are firstly complex problems and involve many parties so that it requires more time, secondly the location of the relevant parties which are difficult to reach, thirdly the bright spots of the Reporting party who do not respond to the completion of the report, and fourthly the lack of good faith from the Reported Party to resolve the problem. If there are reports that are not resolved, the efforts made by the Ombudsman of the Republic of Indonesia Representative for West Kalimantan are to bring in experts and improve communication.Keywords: Ombudsman, Maladministration ABSTRAK Lembaga Ombudsman Republik Indonesia mempunyai tugas untuk menerima laporan atas dugaan malaministrasi penyelenggaraan pelayanan publik. Masyarakat tidak perlu bersusah payah dalam melakukan pelaporan segala bentuk administrasi kepada Ombudsman Republik Indonesia. Begitu juga dengan Ombudsman Republik Indonesia Perwakilan Kalimantan Barat yang memberikan akses seluas-luasnya kepada masyarakat yang mengalami langsung perbuatan maladministrasi yang dilakukan oleh aparat pelaksana dan/atau penyelenggara pelayanan publik. Sejak awal tahun 2022 sampai dengan Juli Ombudsman Republik Indonesia Perwakilan Kalimantan Barat telah menerima 275 laporan pengaduan dugaan maladministrasi.Penelitian ini membahas mengenai Ombudsman Republik Indonesia Perwakilan Kalimantan Barat dalam memproses penyelesaian laporan dugaan maladministrasi serta faktor-faktor yang mengbambat proses penyelesaian laporan dan juga upaya – upaya yang dilakukan Ombudsman Republik Indonesia Perwakilan Kalimantan Barat jika ada laporan yang tidak terselesaikan. Penelitian ini menggunakan jenis penelitian hukum sosiologis dengan pendekatan empiris atau penelitian lapangan yaitu mengkaji ketentuan hukum yang berlaku serta apa yang terjadi dalam kenyataan di masyarakat. Menurut sifat penelitian ini bersifat deskriptif analisis. Adapun objek penelitian ini adalah Lembaga Ombudsman Perwakilan Kalimantan Barat. Teknik yang dipakai yaitu studi dokumen, wawancara dan observasi.Hasil penelitian menunjukkan bahwa di Ombudsman Republik Indonesia Perwakilan Kalimantan Barat jenis dugaan maladministrasi yang paling sering dilaporkan sepanjang tahun 2022 adalah penundaan berlarut , bertindak tidak patut, dan tidak memberikan pelayanan. Faktor yang menjadi penghambat Ombudsman Republik Indonesia Perwakilan Kalimantan Barat dalam proses penyelesaian laporan adalah pertama permasalahan rumit dan melibatkan banyak pihak sehingga membutuhkan waktu yang lebih, kedua lokasi para pihak terkait yang sulit untuk dijangkau, ketiga titik terang pihak Pelapor yang kurang merespon penyelesaian laporan, dan keempat kurangnya itikad baik dari Terlapor untuk menyelesaikan permasalahan. Jika ada laporan yang tidak terselesaikan upaya yang dilakukan Ombudsman Republik Indonesia Perwakilan Kalimantan Barat yaitu mendatangkan ahli serta meningkatkan komunikasi.Kata Kunci : Ombudsman, Maladministrasi